2016
DOI: 10.1542/peds.2015-2851q
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Parent Insurance Ratings, Child Expenditures, and Financial Burden Among Children With Autism: A Mismatch Suggests New Hypotheses to Test

Abstract: OBJECTIVE: Families raising children with autism contribute significant amounts to the cost of care. In this era of health care reform, families have more insurance choices, but people are unfamiliar with health insurance terms. This study uses 2 national data sets to examine health insurance ratings from parents raising children with autism and child expenditures to explore how these measures align. METHODS:Children with autism who met criteria for special health care needs and were continuously insured were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
1
9
0
1
Order By: Relevance
“…To a certain extent, findings from this review are comparable to that yielded from the Western context (e.g., Herring et al, 2006 ; Ekas et al, 2010 ; Ingersoll and Hambrick, 2011 ; Lovell et al, 2012 ; Mackintosh et al, 2012 ; Estes et al, 2013 ; Weiss et al, 2013 ; Rivard et al, 2014 ; Vohra et al, 2014 ; Zablotsky et al, 2014 ; Thomas et al, 2016 ), particularly in regards to social support, severity of autism symptoms, and financial difficulties. However, cultural variations and/or economic differences were found to underlie the differences in how these factors were uniquely manifested and/or experienced in SEA.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…To a certain extent, findings from this review are comparable to that yielded from the Western context (e.g., Herring et al, 2006 ; Ekas et al, 2010 ; Ingersoll and Hambrick, 2011 ; Lovell et al, 2012 ; Mackintosh et al, 2012 ; Estes et al, 2013 ; Weiss et al, 2013 ; Rivard et al, 2014 ; Vohra et al, 2014 ; Zablotsky et al, 2014 ; Thomas et al, 2016 ), particularly in regards to social support, severity of autism symptoms, and financial difficulties. However, cultural variations and/or economic differences were found to underlie the differences in how these factors were uniquely manifested and/or experienced in SEA.…”
Section: Discussionsupporting
confidence: 73%
“…Commonly, the sources of stress in parents of children with ASD include the child's inappropriate and unpredictable behaviors/emotional problems (e.g., Tomanik et al, 2004 ; Herring et al, 2006 ; Lecavalier et al, 2006 ; Osborne and Reed, 2009 ; Estes et al, 2013 ), severity of the autism symptoms (e.g., Osborne and Reed, 2009 ; Ingersoll and Hambrick, 2011 ; Rivard et al, 2014 ), as well as financial worries secondary to the need to spend for treatment intervention and education (e.g., Sharpe and Baker, 2011 ; Vohra et al, 2014 ; Zablotsky et al, 2014 ; Thomas et al, 2016 ). Studies have additionally documented the critical role that social support plays in aiding parents of children with ASD to successfully cope with their higher levels of stress (e.g., Tehee et al, 2009 ; Ekas et al, 2010 ; Lovell et al, 2012 ; Weiss et al, 2013 ); including the importance to gain easy access to and support from mental health professionals (e.g., Mackintosh et al, 2012 ; Vohra et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our study contributes to the growing evidence regarding the benefits of implementing HCBS Medicaid waivers for children with ASD, with other studies finding that Medicaid waivers improve independent living skills and family quality of life, reduce inpatient hospitalizations, and lead parents of Medicaid‐enrolled children with ASD to report that their insurance coverage was adequate and comparable to that of parents of children with commercial insurance . Yet not all states have adopted such waivers, and in states that have adopted waivers, the characteristics of waivers vary substantially across states.…”
Section: Discussionmentioning
confidence: 69%
“…Our study contributes to the growing evidence regarding the benefits of implementing HCBS Medicaid waivers for children with ASD, with other studies finding that Medicaid waivers improve independent living skills and family quality of life, 40 reduce inpatient hospitalizations, 41 and lead parents of Medicaid-enrolled children with ASD to report that their insurance coverage was adequate and comparable to that of parents of children with commercial insurance. 42 Yet not all states have adopted such waivers, and in states that have adopted waivers, the characteristics of waivers vary states may decide to discontinue waivers that they feel are no longer necessary due to EPSDT coverage, which would be most likely to affect those individuals who would not otherwise be Medicaideligible without the waivers. If states wish to continue to reach this population, they will have to ensure that they have a waiver in place that provides services above and beyond those provided by EPSDT.…”
Section: Discussionmentioning
confidence: 99%
“…The most common components of out-of-pocket costs were drug prescriptions, outpatient visits, and dental care. Thomas et al 16 found the following: children who enjoyed private insurance coupled with Medicaid insurance assumed the highest total excess costs, which accumulated to $11,596; children only insured by Medicaid insurance ranked in the middle, with costs of $7238; and children covered by private insurance alone fell in the bottom tier, with costs of $4486. The research by Chatterji et al 17 confirmed that families of children with autism fared worse than families of children with other intellectual disabilities.…”
Section: Direct Costs For Parents Of Children With Autismmentioning
confidence: 99%